Bedryfsgesondheidverpleegkunde - 'n Nuwe Uitdaging Aan Opleidingsinstansies - S.P. Human (AOSIS, 1979)
Research has shown that in South Africa neither the occupational health nurse herself nor management in industry fully appreciate the extent to which she can be utilized if well trained. This article discusses various modifications in occupational health training programmes for nurses in order to ensure greater utilization of these nurses in industry.